2000
DOI: 10.1159/000052221
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endothelin inEarly Renal Cortical Reperfusionin Renal Transplantation

Abstract: The role of specific endothelin receptors in the early renal reperfusion and long-term survival in renal transplantation was investigated in Lewis rats. Left renal transplantation was performed following 2 h cold ischaemia without and with ETA receptor antagonism and following 16 h cold ischaemia with no treatment, with ETA receptor antagonism and with ETB receptor antagonism. The ETA and ETB receptor antagonists, BQ-610 and A-192621 respectively, were add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…We examined ET immunoreactivity in biopsy specimens at 3M after transplantation, correlating ET expression with change in graft function between 3M and 3Y after transplantation. As a caderveric donor kidney is subjected to varying degrees of warm and cold ischemia causing ischemia – reperfusion injury that may lead to acute tubular necrosis (9), we excluded caderveric grafts from study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined ET immunoreactivity in biopsy specimens at 3M after transplantation, correlating ET expression with change in graft function between 3M and 3Y after transplantation. As a caderveric donor kidney is subjected to varying degrees of warm and cold ischemia causing ischemia – reperfusion injury that may lead to acute tubular necrosis (9), we excluded caderveric grafts from study.…”
Section: Discussionmentioning
confidence: 99%
“…All isoforms are products of cleavage of specific prohormones. Prepro‐ET is cleaved to form big‐ET, which in turn is converted by proteases into peptides 21 amino acids in length; the most abundant of these is ET‐1 (8–11). Synthesized by vascular endothelial cells (6, 12), renal mesangial cells (13, 14), glomerular endothelial cells (15) and tubular epithelial cells (16, 17), ET‐1 is well positioned to cause changes in renal vascular tone, particularly cortical vasoconstriction causing reduced renal blood flow and glomerular filtration rate (5, 15).…”
mentioning
confidence: 99%
“…For instance, BQ-123, a selective ET A receptor antagonist, was shown to attenuate the fall in GFR associated with 45 min of renal ischaemia in uninephrectomised rats (Gellai et al 1994). Recently, we have shown that ET A receptor antagonism with BQ-610 during hypothermic preservation improved early post-transplant renal cortical perfusion, renal function and long-term survival (Hammad et al 2000b). …”
Section: Figurementioning
confidence: 99%
“…Recently, we have shown that ET A receptor antagonism with BQ-610 during hypothermic preservation improved early post-transplant renal cortical perfusion, renal function and long-term survival (Hammad et al 2000b).…”
Section: Figurementioning
confidence: 99%
“…Studies have indicated that nonselective endothelin receptor antagonist effectively normalized renal function in diabetic nephropathy [8]. However, blocking both ET A R and ET B R caused long-term renal dysfunction in IRI model [9]. As a result, inhibition of ETaR expression is considered a novel method in the treatment of renal ischemia reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%